Methods and Objectives of Birth Control. A Relational Analysis of the Field of Medicine, Argentina (1930-1940) - Ledesma Prietto, Nadia (2020)
This paper analyzes the ideas and practices regarding birth control promoted by the field of medicine. Employing a relational and gender perspective, differences are found in approaches to contraceptive methods, abortion, and sterilization in Argentina from 1930 to 1940. In a context of demographic transition and the rise of eugenic ideas, voluntary birth control was a problem for the medical elite. In contrast, marginal positionings spread knowledge about access to sexual pleasure without worrying about reproduction.